Let there be light to interact - Stibor, Herwig; Stockenreiter, Maria (Frontiers in Photobiology, 2023)
Light plays a crucial role in ecological dynamics, both as a consumable resource and as an environmental factor. Prokaryotic and eukaryotic photoautotrophs use light as an energy source for photosynthesis, which forms the basis of food chains and determines the flow of energy and matter in ecosystems. Light availability and quality can influence resource complementarity and species coexistence, as well as the stoichiometry of primary producers and the transfer efficiency of food webs. In addition, light serves as an important source of information for organisms, influencing their activities and interactions with the environment. Light shapes biotic interactions, including competition, predator-prey relationships, and mutualistic and antagonistic relationships between photoautotrophs and heterotrophs. Anthropogenic activities affect these photoecological processes, with largely unknown consequences. Hence, understanding the ecological role and control of light is essential for understanding the functioning of ecosystems and biogeochemical cycles.